Cost‐minimization analysis of DTaP‐IPV‐Hib combination vaccine in China: A nationwide cross‐sectional study. Issue 1 (5th December 2022) - Liu, Bei; Cao, Bing; Wang, Chao; Sun, Tao; Miao, Yudong; Zhang, Sihui; Zhao, Tianshuo; Cui, Fuqiang
Abstract: Combination vaccines can reduce the vaccination visit, simplify the vaccination schedule and efficiently improve management. This study was primarily designed to evaluate the economic impact of integrating the diphtheria‐tetanus‐acellular pertussis inactivated poliomyelitis and Haemophilus influenzae type B (DTaP‐IPV‐Hib) combination vaccine into the China National Immunization Program. A cost‐minimization analysis (CMA) compared the costs associated with direct medical, direct nonmedical, and indirect social costs in four schemes was conducted. A budgetary impact analysis assessed the alternative schemes' financial impact on the healthcare budget. Direct medical costs were extracted using a costing questionnaire and an observational time and motion chart. Direct nonmedical (cost for transportation) and indirect costs (loss of productivity) were derived from parents' questionnaires. Replacement of the current vaccination scheme with DTaP‐IPV‐Hib combination vaccine, resulted in net increases in direct medical costs of 77.64% for alternative scheme 1, 146.54% for alternative scheme 2, and 294.67% for alternative scheme 3, respectively. However, the direct nonmedical and indirect costs and the cost of the alternative schemes were 18.18%, 36.36%, and 63.64% lower than the current scheme for alternative scheme 1, alternative scheme 2, and alternative scheme 3, respectively. From the societal perspective, when compared with the current scheme, the budgetary impact of the three alternative schemes were +66 million Chinese Yuan (CNY) (4.81%), +103 million CNY (7.53%), and +305million CNY (22.35%), respectively. The CMA considered a broader perspective of social costs and indicated that the alternative schemes would result in an overall saving of parents' transportation and work loss costs to bring their children for vaccination, translating into a total cost saving of 18.18%, 36.36%, 63.64%, comparing to the current scheme. Thus, fully or partly using the DTaP‐IPV‐Hib combination vaccine is cost‐saving in the context of China.